Diagnostic delay in pulmonary arterial hypertension: Insights from the Australian and New Zealand pulmonary hypertension registry. Issue 8 (30th January 2020) - Khou, Victor; Anderson, James J.; Strange, Geoff; Corrigan, Carolyn; Collins, Nicholas; Celermajer, David S.; Dwyer, Nathan; Feenstra, John; Horrigan, Mark; Keating, Dominic; Kotlyar, Eugene; Lavender, Melanie; et al.
ABSTRACT: Background and objective: Early diagnosis of PAH is clinically challenging. Patterns of diagnostic delay in Australian and New Zealand PAH populations have not been explored in large‐scale studies. We aimed to evaluate the magnitude, risk factors and survival impact of diagnostic delay in Australian and New Zealand PAH patients. Methods: A cohort study of PAH patients from the PHSANZ Registry diagnosed from 2004 to 2017 was performed. Diagnostic interval was the time from symptom onset to diagnostic right heart catheterization as recorded in the registry. Factors associated with diagnostic delay were analysed in a multivariate logistic regression model. Survival rates were compared across patients based on the time to diagnosis using Kaplan–Meier method and Cox regression. Results: A total of 2044 patients were included in analysis. At diagnosis, median age was 58 years (IQR: 43–69), female‐to‐male ratio was 2.8:1 and majority of patients were in NYHA FC III–IV (82%). Median diagnostic interval was 1.2 years (IQR: 0.6–2.7). Age, CHD‐PAH, obstructive sleep apnoea and peripheral vascular disease were independently associated with diagnostic interval of ≥1 year. No improvement in diagnostic interval was seen during the study period. Longer diagnostic interval was associated with decreased 5‐year survival. Conclusion: PAH patients experience significant diagnostic interval, which has not improved despite increased community awareness. Age, cardiovascular and respiratory comorbidities are significantly associated with longer time to diagnosis. Mortality rates appear higher in patients who experience longer diagnostic interval. Abstract : We examined diagnostic delay in a large binational cohort of PAH patients. Mean and median diagnostic intervals were 2.5+/–4.1 and 1.2 (IQR: 0.6–2.7) years, respectively. Age, cardiovascular and respiratory comorbidities were associated with longer diagnostic interval. Mortality was increased in patients with greater diagnostic interval. See related Editorial